2003
DOI: 10.1177/0021998303036265
|View full text |Cite
|
Sign up to set email alerts
|

Free-corner Effects in Cross-ply Laminates: An Approximate Higher-order Theory Solution

Abstract: Like in the well-known free-edge effect situation, stress fields in the vicinity of free corners of layered plates exhibit a distinct three-dimensional and singular behavior and thus represent an important technical situation. Nevertheless, there are only few thorough investigations available concerning stress concentrations near free laminate corners. Since numerical analyses of stress concentration phenomena in composite laminates are computationally expensive, the present contribution is devoted to a simple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 71 publications
(82 reference statements)
0
14
1
Order By: Relevance
“…Thereinto, the meshes have been refined at the location x = 4 mm within the range 0 < y < 6 mm. Again, it can be found that the peak stress near free edge calculated from analytical approach [24,26] is less than the present results. …”
Section: Numerical Examplescontrasting
confidence: 78%
See 1 more Smart Citation
“…Thereinto, the meshes have been refined at the location x = 4 mm within the range 0 < y < 6 mm. Again, it can be found that the peak stress near free edge calculated from analytical approach [24,26] is less than the present results. …”
Section: Numerical Examplescontrasting
confidence: 78%
“…Subsequently, Becker et al [25] adopted an equilibrium stress distribution in conjunction with the principle of minimum complementary energy to describe the free-corner effects of cross-ply laminated plates. In addition, Mittelstedt and Becker [26,27] further developed the approximate higher-order theory to analyze the free-corner problems of laminated plates subjected to thermal loading.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve this methodology, Becker (2003a, 2004b) used an upgraded inplane stress field for laminates with arbitrary nonorthotropic layups. Mittelstedt and Becker (2003b) introduced a simple displacement based approach for pure rectangular cross-ply layups under thermal load by using a higher order single layer theory with trigonometric terms through the complete laminate thickness. Furthermore, Mittelstedt and Becker (2004c,d) employed a layerwise displacement based approach which applies a discretization of symmetric laminates with isotropic layers and cross-ply plates into an arbitrary number of mathematical layers through the plate thickness.…”
Section: Introductionmentioning
confidence: 99%
“…displacement-based equivalent single layer theory with trigonometric thickness terms and an exponential approach has been applied in [9]. Some investigations on the arising corner singularities are also available [10À12].…”
mentioning
confidence: 99%
“…This can be readily explained by the idea of two free-edge effects that interact in the closer corner regions and culminate to some kind of free-corner effect. In fact, the state of stress in the vicinity of free laminate corners is also of a distinct three-dimensional nature and exhibits steep stress gradients that are dominated by a mathematical singularity at the free laminate edges and especially at the free corner [6À12], even though the simple superposition of two freeedge effects to simulate the free-corner problem may lead to false results [8] and in fact is a simplification of the actual situation, which should only be applied for rectangular crossply laminates [8,9]. Nevertheless, even though free laminate corners seem to be an important technical situation as well as the classical free-edge effect in a tensile coupon, there are few investigations available concerning free-corner stress concentrations.…”
mentioning
confidence: 99%